Shotgun Label-free Proteomic Analysis of Clubroot (Plasmodiophora brassicae) Resistance Conferred by the Gene Rcr1 in Brassica rapa - Song, Tao; Chu, Mingguang; Lahlali, Rachid; Yu, Fengqun; Peng, Gary (Frontiers in Plant Science, 2016)
Clubroot, caused by the plasmodiophorid pathogen Plasmodiophora brassicae, is one of the most serious diseases on Brassica crops worldwide and a major threat to canola production in western Canada. Host resistance is the key strategy for clubroot management on canola. Several clubroot resistance (CR) genes have been identified, but the mechanisms associated with these CR genes are poorly understood. In the current study, a label-free shotgun proteomic approach was used to profile and compare the proteomes of B. rapa carrying and not carrying the CR gene Rcr1 upon P. brassicae infection. A total of 527 differentially accumulated proteins (DAPs) were identified between the resistant and susceptible samples, and functional annotation of these DAPs indicates that the perception of P. brassicae and activation of defense responses is triggered via an unique signaling pathway distinct from common modes of recognition receptors reported with many other plant-pathogen interactions; this pathway appears to act in a calcium-independent manner through a not-well defined cascade of mitogen-activated protein kinases and may require the ubiquitin-26S proteasome related to abiotic stresses, especially the cold-stress tolerance. Both up-regulation of defense-related and down-regulation of pathogenicity-related metabolism were observed in plants carrying Rcr1, and these functions may all contribute to the clubroot resistance mediated by this CR gene. These results, combined with those of transcriptomic analysis reported earlier, improved our understanding of molecular mechanisms associated with Rcr1 and clubroot resistance at large, and identified candidate metabolites or pathways for further confirmation of specific resistance mechanisms. Deploying CR genes with different modes of action may help improve the durability of clubroot resistance.